Improved Characterization of Plasma von Willebrand Factor Heterogeneity when Using 2.5% Agarose Gel Electrophoresis - Mazurier, Claudine; Samor, Bruno; Goudemand, Maurice (Thrombosis and Haemostasis, 1986)
Discontinuous sodium dodecyl sulfate electrophoresis in large pore gels, followed by overlay with radiolabelled anti-von Willebrand factor (vWF) antibodies and by autoradiography, permits to analyze the multimeric structure of vWF. The aim of this study was to improve experimental conditions of this technique to satisfactorily resolve the minor forms of plasma vWF while still separating its high, intermediate, and low molecular weight predominant multimers. By using a 2.5% mixture of two selected agaroses, a single electrophoretic analysis of plasma clearly reveals the extreme complexity of the molecular forms of circulating vWF: each multimeric unit of plasma vWF may be separated into five bands, the central one being predominant. The multimeric distribution and “quintuplet” pattern obtained in the electrophoretic system described here permit a convenient classification of the different subtypes of von Willebrand’s disease.
Keywords: von Willebrand factor; von Willebrand’s disease; SDS; agarose electrophoresis